Flexible Sierpinski Carpet Fractal Antenna on a Hilbert Slot Patterned Ground - Vasa Radonić; Keith Palmer; Goran Stojanović; Vesna Crnojević-Bengin (International Journal of Antennas and Propagation)
This paper presents a novel design of fractal antenna on a flexible substrate that operates in UMTS band (universal mobile telecommunication system, 1.92–2.17 GHz). The antenna consists of a Sierpinski carpet fractal radiator, which reduces the overall size of the antenna, and it is realized on top of a Hilbert slot in the ground layer, to achieve required impedance matching. The antenna is compact with the overall dimensions equal to 70 mm × 31 mm × 0.075 mm. Influence that folding has on the initial planar topology is investigated in detail. The obtained results show that the proposed antenna is more tolerant to folding than the conventional patch and that it exhibits relatively stable radiation patterns even when folded in complex manners.